2019
DOI: 10.3390/ijms20092079
|View full text |Cite
|
Sign up to set email alerts
|

Development-Related miRNA Expression and Target Regulation during Staggered In Vitro Plant Regeneration of Tuxpeño VS-535 Maize Cultivar

Abstract: In vitro plant regeneration addresses basic questions of molecular reprogramming in the absence of embryonic positional cues. The process is highly dependent on the genotype and explant characteristics. However, the regulatory mechanisms operating during organ differentiation from in vitro cultures remain largely unknown. Recently, miRNAs have emerged as key regulators during embryogenic callus induction, plant differentiation, auxin responses and totipotency. Here, we explored how development-related miRNA sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Transcriptomic datasets on Zea mays embryogenic cultures have shown that the expression pattern of individual auxin-related miRNAs is dependent on the genotype and the age of a culture [66][67][68]78]. The diversity of the miRNA expression profiles in embryogenic cultures, for example, the up-vs. downregulation of the same miRNA, could reflect the complexity of the miRNA-mediated regulatory pathways that fine-tune the somatic cell transcriptome towards embryogenic development in response to specific endo-and exogenous culture factors.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic datasets on Zea mays embryogenic cultures have shown that the expression pattern of individual auxin-related miRNAs is dependent on the genotype and the age of a culture [66][67][68]78]. The diversity of the miRNA expression profiles in embryogenic cultures, for example, the up-vs. downregulation of the same miRNA, could reflect the complexity of the miRNA-mediated regulatory pathways that fine-tune the somatic cell transcriptome towards embryogenic development in response to specific endo-and exogenous culture factors.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
“…Numerous MIRNA genes, including members of the same gene family of SE-modulated expression, have been reported in transcriptomic analyses of different plant cultures [55,58,66,68,73,79]. The expression of different MIRNA gene family members is strictly regulated during plant development in an organ-and tissue-specific manner [80,81], and thus reporter line analyses could be important in identifying the specific MIRNA genes that contribute to SE induction.…”
Section: Auxin-related Mirnas Fine-tune the Genetic Network That Contmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a way, the tissues may elicit developmental responses when endogenous auxin redistributes. The current panorama on specific EC features depicts greater accumulation of tasiR-ARF biogenesis components and ZmARF3 transcripts, expression of PIN auxin polar transporters and enrichment in auxin response-related miRNAs and targets [32]. This information provides insights into the genetic program underlying de novo plant formation, where leaf initiation and morphogenesis appear as primary and essential processes.…”
Section: Discussionmentioning
confidence: 87%
“…All analyses were performed with maize calli induced from Tuxpeño VS-535 immature embryos. After subcultures for 8-12 months on N6 proliferation medium (see methods) calli were separated in embryogenic (EC) and non-embryogenic (NEC) types according to their morphology (Supplementary Materials Figure S1; [32]). For plant regeneration, phytohormones were gradually depleted under a photoperiod.…”
Section: Maize Tas3 and Tasir-arf Components Gene Expressionmentioning
confidence: 99%